The effects of octreotide on gastric lesions and gastric mucosal barrier in rats which applied stress - Cihat GÜZEL,; Zeki KANAY,; Abdurrahman ÖNEN,; Doğan KURT,; Orhan DENLİ,; Fikri CANORUÇ, (Turkish Journal of Gastroenterology, 2019)
-